KONTRUKSI SOSIAL ATAS WARISAN BUDAYA SUNAN KUDUS The Social Construction of Sunan Kudus Cultural Legacy - Dandung Budi Yuwono (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
Ethnic-religious based conflicts which are often occurred in many part of Indonesia are examples on how complicated of the ethnic problems in this country. On the other hand, Kudus regency that consists of society with different ethnic and religion is free from such ethnic-religious based conflict. The goal of this study is to explore the social movement done by Sunan Kudus in building multiculturalism of Kudus community, to understand the life of Kudus society in holding culture of multiculturalism, to know the relevance of such multiculturalism in the mid of various challenge in this continuous changing age. This study uses a qualitative approach. Data were collected through these ways; observation, participant observation, and in-depth interview. Data were analyzed using interpretive way, triangulation analysis with emic and ethic perspective. The findings of this study indicate the condition of religious harmony that is manifested in the social space of the communities in Kudus that are inseparable from these supporting factors: (1) awakening of multiculturalism awareness among communities in Kudus initiated by Sunan Kudus; (2) socially preserving and reproducing of the inherited multiculturalism culture initiated by Sunan Kudus, and (3) the strong image of society towards Sunan Kudus as the charismatic figure.